Self-adaptive rolling motion for snake robots in unstructured environments based on torque control - Shihao Ma; Fatao Qin; Shufan Chen; Longchuan Li; Jianming Wang; Zengzeng Wang; Shuai Li; Xuan Xiao (Biomimetic Intelligence and Robotics, 2023)
Snake robots have great potential for exploring and operating in challenging unstructured environments, such as rubble, caves, and narrow pipelines. However, due to the complexity and unpredictability of unstructured environments, designing a controller that can achieve adaptive motion is crucial. This paper proposes a self-adaptive torque-based rolling controller for snake robots, enabling compliant motion in unstructured environments. First, a controller is designed to modify the torque of each motor by focusing on the different motion states of the rolling gait. Second, an experimental platform is established for snake robots to verify the effectiveness of the controller. Finally, a series of rolling experiments are conducted using the torque-based rolling controller. In conclusion, the self-adaptive torque-based rolling controller enhances snake robot adaptability and mobility.